The Virtues and Vices of Agnosticism - Charles Champe Taliaferro (Philosophies, 2024)
This essay begins with preliminary observations about the nature of agnosticism. Based on the term’s etymology, in this essay an agnostic about some proposition (e.g., God exists) is someone who does not know whether the proposition is true. Being an agnostic about the truth of a proposition is compatible with the proposition appearing to be true or the state of affairs obtains but incompatible with an agnostic knowing its truth or that the state of affairs obtains. (Reference to propositions and states of affairs is intended to be inclusive, rather than a controversial metaphysical distinction.) Based on apparent virtues and vices, reasons are offered about when agnosticism (or the profession of agnosticism) is virtuous or philosophically desirable and when either actual agnosticism or its profession seems to be a vice or undesirable. The essay concludes with challenging Anthony Kenny’s case for agnosticism about theism based on the virtue of humility. The central claims about apparent virtues and vices rest on the positive epistemic standing of appearances as defended by many so-called “common sense philosophers” Thomas Reid, Roderick Chisholm, and, more recently, Thomas Nagel’s thesis about the justified status of the appearance of values.